La vocación ontológica en el pensamiento de Rafael García-Herreros (2018)
The following essay endeavors to present an analysis of the ontological concept within the insight of the priest Rafael García-Herreros. Regarding the speeches of García-Herreros, which comprehend a wide range of oral and written discourses, this essay tends to clarify the analysis of García-Herreros subject concept. Notwithstanding, to do it so the comprehension about human integrity resolved as an emergent agent and as well as a vivid participant between the relationship with other subjects and the world. Above all, the aim of this essay is to set a contribution in which the ontological insight of García-Herreros’ offers a conception and meaning for being a teacher. Moreover, this particular way of thinking is shaped by an ontological performance model, based as well, on the will, the knowledge and the power of transforming society through a dialectical process over the joint of human practices within the inner and external world. In the same way, this paper will try to comprehend the link between the ontology insight and the pedagogy practice, thus these are bounded and together, they contribute to the praxeological pedagogy focus, in which teachers are self-conscious about the reflexiveness of their deeds.